2019
DOI: 10.1097/prs.0000000000005839
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Adipose-Derived Stromal Cells with Breast Cancer Cell Lines

Abstract: Background: Assisted lipotransfer for breast reconstruction involves the isolation and supplementation of adipose-derived stromal cells. This procedure has raised concerns regarding safety with respect to promotion of tumor growth and relapse. Several in vitro and animal experimental studies have indicated increased survival, growth, and invasive characteristics of breast cancer cells on interaction with adipose-derived stromal cells. These results seem to be in poor concordance with clinical obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…A fibrinogen matrix stimulates a two-fold increase in BM-MSC cell yield over plastic surfaces without affecting differentiation 52 . The significance of the multitude of adipokines altered in response to metformin is difficult to interpret but increase of osteogenic signals, activation of immune processes and inhibition of MMP9 is expected to be beneficial for patients 53 .…”
Section: Western Blot Results Of Adipokine Expression Of the Bm-mscsmentioning
confidence: 99%
“…A fibrinogen matrix stimulates a two-fold increase in BM-MSC cell yield over plastic surfaces without affecting differentiation 52 . The significance of the multitude of adipokines altered in response to metformin is difficult to interpret but increase of osteogenic signals, activation of immune processes and inhibition of MMP9 is expected to be beneficial for patients 53 .…”
Section: Western Blot Results Of Adipokine Expression Of the Bm-mscsmentioning
confidence: 99%
“…The exosomes, released from the adipocyte s and ASCs, are emerging as a new type in the crosstalk between breast tumors and adipocytes ( Sauter et al, 2019 ; Teufelsbauer et al, 2019 ). Previously, Lin et al (2013) investigated the effect of ASC-exos on breast cancer MCF7 cells, showing that ASC-exos activated the Wnt and Hh signaling pathways to strengthen tumor cell migration.…”
Section: Asc-exos In Breast Cancer and Breast Reconstructionmentioning
confidence: 99%
“…In particular, the possibility cannot be ruled out that ASCs may stimulate dormant breast cancer cells after CAL in patients with a mild deformity after mastectomy for breast malignancy. To date, several studies, including in vitro and in vivo experiments, have investigated this issue and reported markedly controversial findings [50][51][52][53]. A clinical analysis of a large series of autologous fat grafts without supplementation with ASCs for breast reconstruction demonstrated a low complication rate and no evidence of increased oncologic risk [54][55][56][57].…”
Section: Safetymentioning
confidence: 99%